Sterically Hindered Derivatives of Pentacene and Octafluoropentacene - Schroeder, Zachary W.; Rezghi Rami, Parisa; Adam, Matthias; Ferguson, Michael J.; Hampel, Frank; Tykwinski, Rik R. (Chemistry - A European Journal, 2024)
6,13-Diethynylpentacene derivatives with sterically bulky substituents (Tr*, tris(3,5-di-tert-butylphenyl)methyl groups) appended to the ethynyl moieties at the 6- and 13-positions have been synthesized, as well as derivatives with electron-withdrawing fluorine groups on the 1,2,3,4,8,9,10,11-positions. These molecules are designed to investigate relationships between steric and electronic effects on the stability of pentacene toward endoperoxide formation via reaction with photosensitized oxygen in solution under ambient light (i. e., ‘laboratory’ conditions). It is evident from the study that stabilization through changes to the electronic characteristics of pentacene are more effective than the incorporation of sterically bulky groups at the acetylenic termini. Selected pentacene derivatives have been made into binary, amorphous films with the fullerene derivative PCBM to investigate the stability imparted by substituents against cycloaddition reactions. Overall, the introduction of steric protection through the incorporation of Tr* groups is not an efficient strategy for enhancing the persistence of pentacenes. Stabilization through fluorination proves successful for extending the lifetime of the pentacene derivatives by an order of magnitude in solution. Notably, the persistence of pentacene derivatives in solution can also be enhanced through the use of ethereal solvents stabilized with butylated hydroxy toluene (BHT) and/or an increased number of trialkylsilyl groups as substituents.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Acene stability; Endoperoxide; Organic semiconductor; Pentacene; Stability; Steric hindrance